Administrative and financial corruption in Iraq: Problems - Effects - Treatments - Ali Hassan, Raghad (Al-Adab Journal, 2019)
Corruption has become a major challenge for the peoples of the world in all its countries and democratic political systems, or autocratic, and have consequences for the entire political, economic and social life, which was referred to in this study. As the increase in the probability of spreading corruption in countries that suffer from political instability and the continuous changes in the systems of countries and their laws, which leads to the lack of stable political institutions and systems of matter and accounting and control of public funds and this leads to the lack of transparency in the executive work and other government works and from 2003 to the year 2013 Iraq occupies the advanced ranks of Transparency International’s Corruption Perceptions Index. To be described as one of the most corrupt countries in the world, which is now undermining the development process and advancement in Iraqi society and the building of political institutions active and stable as well as reduce investment opportunities. This result reached by Iraq recently can be traced back to many and varied factors interacting with each other constantly to threaten the fabric of Iraqi society and political life as a whole. Perhaps the most prominent of these factors are political instability and the lack of social awareness and policies of occupation and the adoption of methods of political quotas, sectarianism and nationalism in the administration of the state and its emerging institutions. Immunity for senior executives and legislators of the Iraqi state and leaders of political parties. Corruption in any country or international or regional system is undoubtedly an indication of the imbalance in public administration in general and a real reflection of the lack of good governance and effective mechanisms and opposition to this phenomenon.